DISCUSSING MARGINALITY: A REFLECTION FROM THE URBAN AND SOCIAL GEOGRAPHY PERSPECTIVE - Fabio Amato (Bollettino della Società Geografica Italiana)
The paper focuses on the term marginality and its use in social sciences and in human geography in particular. Quite surprisingly, geographical knowledge seems not very committed to define precisely the concept of marginality, probably because of the wider use of the concept of periphery or because of the sociological orientation usually given to the term. When used, the concept of marginality is affected by a negative connotation, due to the fact that it has always been opposed to the notion of centre. By means of examples, the paper explores the possible definitions of marginality and it stresses the importance to consider the geographical dimension of marginality. The paper also highlights the strategic role of considering the margins in the shaping of innovative and original perspectives and scenarios on the changing contemporary world.